The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 6 Breakfast. Dinner. Tea. 4. ⅓ pt. Milk Boiled Egg Rusks : Margarine Vegetable and Cheese (¼ oz.) Hot-pot Potatoes Chocolate Queen of Puddings ⅓ pt. Milk Salad and Date or Sultana Sandwiches 5. ⅓ pt. Milk Oatcakes with Tomato or grated Carrot Bread : Margarine Minced Meat and Vegetable Roly-poly Potatoes Root Vegetables Cocoa Cap Custard ⅓ pt. Milk Salad Sandwiches Scones and Seedless Jam 6. ⅓ pt. Cocoa Fried Bacon (1 oz.) and Fried Potatoes Rusks : Margarine Salad : Cheese (¼- oz. grated) Wheatmeal Bread : Margarine Raw Sultanas ⅓ pt. Milk ⅓pt. Milk Mock Lemon Curd Sandwiches Oatmeal Biscuits 7. ⅓ pt. Milk Porridge Toast : Margarine Fish (steamed or baked) Mashed Turnips Potatoes Castle Pudding ⅓ pt. Milk Salad Sandwiches Oatcakes and Seedless Jam 8. ⅓ pt. Cocoa Scrambled Egg (½) Toast : Margarine Boiled Bacon (2 oz.) Salad Baked Potatoes Fruit Mould ⅓ pt. Milk Wheatmeal Bread : Margarine Plain Cake 9. ⅓ pt. Cocoa Porridge (3 oz.) Toast : Margarine, Yeast Extract Cress Mutton and Lentil Hot-pot Potatoes Carrots Milk Pudding or Trifle ⅓pt. Milk Wheatmeal Scones Seedless Jam and Margarine 10. ⅓ pt. Milk Boiled Egg Toast: Margarine Vegetable Soup made with Milk Seedless Jam Roly-poly ⅓ pt. Milk Cheese and Salad Sandwiches 11. ⅓ pt. Milk Bacon (1 oz.), Fried Bread Bread : Margarine Shepherd's Pie Root Vegetable Semolina Whip ⅓pt. Milk Salad and Marmite Sandwiches Bread : Margarine 12. ⅓ pt. Milk Porridge Rusks : Margarine Fish Pie Green Vegetables Brown Betty ⅓ pt. Milk Cocoa and Dried Milk Sandwiches 127/NU/5/5/1/28